Emergency microsurgical trapping, decompression, and revascularization of a middle cerebral artery dissecting aneurysm using a minipterional approach in a pediatric patient: illustrative case - Albiña-Palmarola, Pablo; Díaz-Peregrino, Roberto; Muñoz, Sebastian; Lopez, Eduardo; Henkes, Hans; Mura, Jorge (Journal of neurosurgery. Case lessons, 2024)
BACKGROUND Pediatric intracranial aneurysms present unique diagnostic and therapeutic challenges due to their rarity and their distinct anatomical and physiological considerations compared with those of adult intracranial aneurysms. The authors present the case of a symptomatic pediatric patient who required emergency microsurgical treatment after a thrombosed dissecting aneurysm was identified in the right M1 segment of the middle cerebral artery. OBSERVATIONS The lesion completely occluded its parent vessel, although distal blood flow was reconstituted through leptomeningeal collaterals. However, aneurysm wall contrast enhancement and signs of early perfusion changes were noticed, which prompted emergency treatment consisting of microsurgical aneurysm trapping, decompression, and extracranial/intracranial revascularization to be successfully performed through a minipterional craniotomy. After 1 year, the bypass occluded, although the patient remained asymptomatic. A slight enlargement of the ipsilateral anterior cerebral artery suggested the possibility of a benign hemodynamic rearrangement. LESSONS Emergency treatment may be necessary when signs of lesion instability or hemodynamic compromise are present; however, a comprehensive multidisciplinary evaluation is required. Treatment of complex vascular lesions using a minipterional approach is feasible even in pediatric patients, and delayed bypass occlusion may be a benign phenomenon reflecting gradual blood flow reorganization. https://thejns.org/doi/10.3171/CASE24484
Gesehen am 17.09.2025